Modeling of cooking and phase change of egg white using computational fluid dynamics - Rubén E. Sánchez-García; Orlando Castilleja-Escobedo; Rodrigo Salmón-Folgueras; José Luis López-Salinas (Current Research in Food Science)
This study proposes simulating the cooking of eggs by modeling fluid egg products as phase-change materials (PCMs) within a computational fluid dynamics (CFD) model. A simplified physical prototype was built to conduct experiments to tune a simpler version of the mathematical model. The information was later used to build a complete mathematical model of a real egg that was compared with experimental data. Phase transition temperature ranges, and the energy required to initialize the transition were specified. Heat transfer coefficients were estimated for both models. Experiments for thermal processing and phase change were conducted at temperatures between 90 and 100 °C. The real egg model was validated with experimental data reported elsewhere. The simulations assess the time required to cook an egg (800–1200 s), demonstrating a homogeneous increase in temperature and phase transition. However, potential overestimation in simulations was observed, likely due to differences in quantifying techniques and non-uniform cooking processes.